The Impact of MDT‑Based Collaborative Nursing Education on Emotional Well‑Being and Quality of Life in IBD Patients: A Randomized Controlled Trial - Li, Xixi; Wang, Xiquan; Chen, Linlin; Zhou, Tong; He, Lin; Tan, Lin; Yuan, Qin (Celebes Nursing Journal, 2025)
Introduction: Traditional discharge education for inflammatory bowel disease (IBD) patients tends to be brief and one-way, often leaving gaps in knowledge, self-care, and emotional support. The LEARNS model, a structured and interactive health education programme, may be more effective in addressing these needs and improving patient outcomes. Objective: To assess the impact of a LEARNS-based nursing education program on anxiety, depression, self-care ability, disease knowledge, and health-related quality of life in patients with inflammatory bowel disease. Methods: In a randomized controlled trial conducted at a tertiary hospital in 2024, 120 adult IBD inpatients were randomly assigned to either 12 weeks of LEARNS-based education combined with standard care (n = 60) or to standard care alone (n = 60). We assessed anxiety (Zung Anxiety Scale), depression (Zung Depression Scale), self-care ability (ESCA), disease knowledge (CCKNOW), and quality of life (IBDQ) at baseline and after 12 weeks of intervention. Results: After 12 weeks, the LEARNS group showed significantly lower anxiety (27.2 ± 5.0 vs. 32.0 ± 6.2, p < 0.001) and depression (31.7 ± 7.6 vs. 36.8 ± 9.6, p = 0.012) scores. Additionally, the LEARNS group had significantly higher self-care scores (130.2 ± 17.3 vs. 117.8 ± 13.6, p < 0.001) and knowledge scores (15.6 ± 3.0 vs. 12.9 ± 2.6, p < 0.001). However, there were no significant differences between the two groups in quality-of-life scores (IBDQ) (p = 0.83). Conclusion: The LEARNS health education model significantly improved anxiety, depression, self-care, and disease knowledge in IBD patients over 12 weeks. However, there was no significant improvement in quality of life, which highlights the need for further studies with longer follow-up to explore the long-term effects of the intervention. Integrating this patient-centered education approach into routine clinical practice can provide enhanced support for patients, but future multicenter studies with extended follow-up are necessary to confirm the lasting impact on quality of life.